1989
DOI: 10.1267/ahc.22.669
|View full text |Cite
|
Sign up to set email alerts
|

Alternate coexistence of NADPH-diaphorase with choline acetyltransferase or somatostatin in the rat neostriatum and basal forebrain.

Abstract: The coexistence of reduced nicotinamide adenine dinucleotide phosphate diaphorase (NADPH-d) with somatostatin (SOM) and choline acetyltransferase (ChAT) was compared between the rat neostriatum (ST) and basal forebrain complex (BF). NADPH-d coexists with SOM in ST, but not in the ventral pallidum (VP), in the substantia innominata-nucleus basalis complex (SI-NB) and in the magnocellular preoptic nucleus (NPM) of the BF. In the medial septal nucleus as well as in the vertical and the horizontal limbs of the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Interestingly, cholinergic interneurons were frequently seen in the hippocampus but were scarce in neocortical areas. Analysis of the neurochemical heterogeneity of cholinergic cell populations in rabbit BFB revealed the sparse occurrence of CB (ϳ19%) and nNOS (Ͻ1%) in cholinergic neurons of posterior MBN, a finding that provides a phylogenetic niche for the rabbit forebrain cholinergic system between rodents (with partial nNOS coexpression; Schober et al, 1989;Brauer et al, 1991;Geula et al, 1993) and primates (with partial CB coexpression; Chang and Kuo, 1991;Côté and Parent, 1992;Geula et al, 1993;Ichitani et al, 1993;Hä rtig et al, 2002). This assumption is further supported by recent phylogenetic concepts indicating that the rabbit, a member of the mammalian order Lagomorpha, has a distant relationship to members of the orders of both Rodentia and Primates (Benton, 2000).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, cholinergic interneurons were frequently seen in the hippocampus but were scarce in neocortical areas. Analysis of the neurochemical heterogeneity of cholinergic cell populations in rabbit BFB revealed the sparse occurrence of CB (ϳ19%) and nNOS (Ͻ1%) in cholinergic neurons of posterior MBN, a finding that provides a phylogenetic niche for the rabbit forebrain cholinergic system between rodents (with partial nNOS coexpression; Schober et al, 1989;Brauer et al, 1991;Geula et al, 1993) and primates (with partial CB coexpression; Chang and Kuo, 1991;Côté and Parent, 1992;Geula et al, 1993;Ichitani et al, 1993;Hä rtig et al, 2002). This assumption is further supported by recent phylogenetic concepts indicating that the rabbit, a member of the mammalian order Lagomorpha, has a distant relationship to members of the orders of both Rodentia and Primates (Benton, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…In the rat, distinct subpopulations of cholinergic projection neurons are immunoreactive for nNOS (Schober et al, 1989;Brauer et al, 1991;Geula et al, 1993). In contrast, nNOS is entirely absent in cholinergic projection cells of primates (Geula et al, 1993;Wu et al, 2000), where ChAT-and nNOS-positive neurons form nonoverlapping populations throughout the "Ch1"-"Ch4" regions.…”
Section: Neurochemical Heterogeneity Of Cholinergic Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in different regions of the rat brain have shown that ND is expressed by neurons containing acetylcholine (Vincent et al, 1983b,c;Vincent, 1986;Schober et al, 1989); y-aminobutyric acid (GABA) (Vaney and Young, 1988;Hedlich et al, 1990); enkephalins (Roberts and Difiglia, 1988); somatostatin (Vincent et al, 1983a;Vincent, 1986;Scott et al, 1987;Sharp et al, 1987;Alonso et al, 1992b); neuropeptide Y, C-PON, and avian pancreatic polypeptide (Vincent et al, 1983a;Scott et al, 1987;Villalba et al, 1988Villalba et al, , 1989; calretinin ; and CaBP (Alonso et al, 1992a. However, for all these substances there are only regional or partial overlaps and coexpressions, and the unique general coexistence is with nitric oxide synthase (Dawson et al, 19911, and with citrulline, a byproduct in nitric oxide synthesis (Hope et al, 1991).…”
Section: Nadph-diaphorase Stainingmentioning
confidence: 94%
“…One of these cholinergic subpopulations in the rostral BF is the outer assembly of cholinergic cells near the margin between hDB and VP. These cells have never shown coexpression of NADPHdiaphorase histochemistry (16), contrary to other cholinergic subpopulations where double-labelling occurs. It cannot be excluded that not yet known functional interrelations with regard to these findings and the specificity of galanin containing fibre innervation may exist.…”
Section: Discussionmentioning
confidence: 61%